Maternal and child care, service used and socio-demographic characteristics in a city in the inner state of Paraíba, Brazil - Figueroa Pedraza, Dixis; Araújo, Erika (Journal of Health Care, 2017)
Objective: To analyze the prenatal and delivery/postpartum care in the city of Campina Grande, Paraíba (BR), considering maternal sociodemographic characteristics, according to the service used (public or priÂvate). Methods: Cross-sectional study developed in the city of Campina Grande, Paraíba. A total of 738 mothers of children under one year of age were interviewed, and information included sociodemographic status and prenatal, delivery and postpartum care and type of service used. The distribution related to the type of service used in the prenatal and delivery/postpartum was analyzed according to maternal socioÂdemographic characteristics. Results: The use of public services was 77% in prenatal care and 80.1% in cases of delivery/postpartum among these mothers. There was a systematic advantage in the use of public health services for prenatal and delivery/postpartum by women with less education and families benefited from the Programa Bolsa Família (Brazilian’s "Family Allowance Program"). Conclusion: The results sugÂgest that the increased use of public health services coexists with inequalities in the use of health services among population served by SUS (Public Health System) and populations assisted by private health plans. Thus, there is a need for actions to improve prenatal care and delivery/postpartum, especially by the public sector for populations of greater vulnerability.